1993
DOI: 10.3109/02688699309103475
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences between Maori and European New Zealanders in aneurysmal subarachnoid haemorrhage

Abstract: Racial differences in the incidence and rate of rupture of intracranial aneurysms are well recognized. A retrospective study of racial differences between Maori and European New Zealanders presenting to the Auckland Regional Neurosurgical Unit between 1985 and 1990 was conducted. It was found that the incidence per 100,000 of the population for all aneurysms was 14.3 for Europeans and 25.7 for Maoris. The mean age at rupture was 10 years earlier in Maoris with single aneurysms. A strong association between ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…First, we studied SAH mortality rates and it is not known whether the differences we observed were due to differences in incidence or case fatality rates. The few studies that have compared case fatality rates for SAH among racial groups have found very similar rates [5][6][7]11], indicating that differences in the incidence rates are the most likely explanation for the differences in the mortality rates we observed. Second, in our analysis only death certificate data were used and a careful review of all patient data was not performed.…”
Section: Discussionmentioning
confidence: 45%
“…First, we studied SAH mortality rates and it is not known whether the differences we observed were due to differences in incidence or case fatality rates. The few studies that have compared case fatality rates for SAH among racial groups have found very similar rates [5][6][7]11], indicating that differences in the incidence rates are the most likely explanation for the differences in the mortality rates we observed. Second, in our analysis only death certificate data were used and a careful review of all patient data was not performed.…”
Section: Discussionmentioning
confidence: 45%
“…Even though rare, aneurysms have been described in this age group. [21,23] Age as an idependent variable may suggest that ethnic [19,29] and genetic [30] factors influence the age at presentation. Aneurysms are more common in women over 50 years of age [5,8,31] and also some studies have Multiple 21-30 2 ------31-40 7 ------41-50 5 1 2 5 ---51-60 3 13 5 -2 -1 61-70 2 1 3 -2 --71-80 1 ----1 -Total counts 20 15 10 5 4 1 1 reported that the female gender is risk factor for both formation and growth of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…5 In New Zealand, it has been shown that Maoris and Pacific Islanders have a much greater risk of SAH than the Caucasian population. 6,7 It is not known whether there are similar differences in the incidence of SAH between different racial groups within Australia.…”
mentioning
confidence: 96%